Pendidikan Islam Berbasis Kearifan Lokal: Memperkuat Identitas Budaya Melalui Kurikulum Merdeka - Putri, Rani Awalia; Ondeng, Syarifuddin; Yahdi, Muh. (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to examine the implementation of local wisdom-based Islamic education in the context of the Independent Curriculum and its impact on strengthening cultural identity in Indonesia. In the era of rapid globalization, local wisdom-based education has an important role in maintaining cultural values that are the identity of the nation. This study uses a library research method to analyze various literature related to Islamic education, local wisdom, and the Independent Curriculum. The results of the study indicate that the integration of Islamic values with local culture through education can shape the character of students who respect their cultural heritage. In addition, the implementation of the Independent Curriculum provides flexibility for educators to develop teaching materials that are appropriate to local conditions and needs, thereby strengthening the relationship between religion and culture. Local wisdom-based Islamic education, which combines religious teachings and traditional culture, has been proven to strengthen the cultural identity of students amidst the flow of globalization. Although there are challenges in its implementation, local wisdom-based education has great potential to maintain and strengthen Indonesia's cultural heritage. This study suggests the need for further support from the government and educators to ensure that the implementation of this education can take place effectively and have a positive impact on the nation's next generation.